2009
DOI: 10.1074/jbc.m109.037267
|View full text |Cite
|
Sign up to set email alerts
|

A Turn-like Structure “KKPE” Segment Mediates the Specific Binding of Viral Protein A27 to Heparin and Heparan Sulfate on Cell Surfaces

Abstract: ). Importantly, T22K/A25K retained the binding specificity for HP and HS but not chondroitin sulfate, as shown by in vitro SPR and in vivo cell adhesion and competitive binding assays. Molecular modeling of the HBS was performed by dynamics simulations and provides an explanation of the specific binding mechanism in good agreement with the site-directed mutagenesis and SPR results. We conclude that a turn-like structure introduced by the KKPE segment in vaccinia viral envelope protein A27 is responsible for it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…2A) shows only the signals originating from the flexible random coil (21-42 residues), whereas any remaining signals arising from the structured domains, such as CCD, DLD, and LZD (i.e. the A17 binding domain), were absent, consistent with the truncated A27 crystal structure (27) and previous reports (24,26,44). In contrast, as shown in Fig.…”
Section: A27 Binds To the N Terminus Of A17 As Revealed By Hsqc-supporting
confidence: 39%
See 3 more Smart Citations
“…2A) shows only the signals originating from the flexible random coil (21-42 residues), whereas any remaining signals arising from the structured domains, such as CCD, DLD, and LZD (i.e. the A17 binding domain), were absent, consistent with the truncated A27 crystal structure (27) and previous reports (24,26,44). In contrast, as shown in Fig.…”
Section: A27 Binds To the N Terminus Of A17 As Revealed By Hsqc-supporting
confidence: 39%
“…Previous studies have suggested that the N-and C-terminal domains are structurally distinct. For instance, the HBS is a flexible random coil, whereas the CCD, DLD, and LZD form rigid consecutive heptad repeated coiled coils (25,26). Despite their structural differences, both the N-terminal HBS and the C-terminal coiled coils cooperatively provide the specificity required for the interaction of the A27 protein with HS on the cell surface (26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several methodologies have been used to study HSPG interactions, including mapping using synthetic peptides (21,34), site-directed mutagenesis (17,47,62), molecular modeling (2,4,30,47,51), high-resolution nuclear magnetic resonance (NMR) spectroscopy (2,25,47), X-ray crystallography (24,33,46), and hydrodynamic measurements (28). An early work based on heparin binding protein sequence comparisons in HIV-1 led to the proposition that two consensus heparin binding sequences, XBBXBX and XBBBXXBX motifs (where B stands for a basic and X for a neutral/hydrophobic amino acid), dictated such interactions (4).…”
mentioning
confidence: 99%